The Influence of The Question Box Media Assisted Teams Games Tournament Model on Science Learning Outcomes at Elementary School - Zulherman Zulherman; Khairil Iba; Andhini Ayu Paramita; Supriansyah Supriansyah; Galih Baskoro Aji (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2021)
This study aims to provide an empirical picture of whether or not the Teams Games-Tournament (TGT) learning model aided by Question Box media has an impact on the fourth-grade science learning outcomes at SDN Cengkareng Barat 16 Pagi West Jakarta in the second semester of the 2018/2019 academic year. The research population consisted of 55 students consisting of 28 students of class IV A and 27 students of IV B. The sampling technique used is saturated sampling. This study used a quantitative approach, and the research method used was a quasi-experimental design with a Nonequivalent Posttest-Only Control Group Design. The result showed an effect of the Teams Games-Tournament (TGT) learning model assisted by the question box media on student learning outcomes in science.